Enhancing Conceptual Understanding through Networked Collaborative Learning : A Study on Preservice Teacher - Zulnuraini; Punaji Setyosari; Saida Ulfa; Dedi Kuswandi (Attractive : Innovative Education Journal, 2025)
The development of learning social network applications or features makes it possible to develop collaborative activities, making it easier for individuals in groups to communicate. NCL combines technology where social media and web technology are used to support relationships between learners, learning resources and learning communities. The purpose of this study was to determine the effect of NCL on concept understanding. The method used was descriptive quantitative approach with quasi experimental design. The sampling technique used purposive sampling with a total sample of 158 PGSD students at Tadulako University. Data collection techniques through tests in the form of pre-test and post-test statements of learning outcomes of concept understanding. The results of hypothesis testing showed that there was no significant difference in learning outcomes of concept understanding between the group taught with the networked collaborative learning strategy and the group that learned with discussion. The results of this study found that NCL applied did not affect the concept understanding of learners. Thus, NCL has not been proven to be more effective than conventional in the context of concept learning in this study